Construction and validity of educational technology about the human papillomavirus vaccine for adolescents - Paula Gisely Costa Silva; Ilma Pastana Ferreira; Lidiane Assunção de Vasconcelos; Haroldo Gonçalves de Jesus; Tobias Ferreira Gonçalves; Ivonete Vieira Pereira Peixoto (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to construct and validate an educational technology in comic book format about the human papillomavirus vaccine aimed at adolescents. Methods: a methodological study, with a quantitative approach, through the agreement method. It was carried out in two phases: educational technology construction and content validity. Participants are expert judges in the health field. Data collection took place in a virtual environment, through a questionnaire. Data analysis was performed by calculating the Content Validity Index. A Content Validity Index of at least 80% was accepted. Results: the comic book's overall Content Validity Index was 82%, reaching the minimum limit established to be validated. Conclusions: comics are fundamental in the teaching-learning process, aiming to catch adolescents' attention. Therefore, it is characterized as a valid tool to inform, in a playful manner, about the human papillomavirus vaccine.